Glutathione‐S‐transferase P1, early exposure to mould in relation to respiratory and allergic health outcomes in children from six birth cohorts. A meta‐analysis. Issue 3 (18th January 2013) - Tischer, C. G.; Gref, A.; Standl, M.; Bauer, M.; Bergström, A.; Brauer, M.; Carlsten, C.; Gehring, U.; Granell, R.; Henderson, J.; Kerkhof, M.; MacNutt, M.; et al.
Abstract Background There are conflicting study results regarding the association of exposure to visible mould and fungal components in house dust with respiratory and allergic diseases in children. It has been suggested that functional polymorphisms of the GSTP1 gene may influence the risk for allergic disorders through an impaired defence against oxidant injury. Methods We examined in six birth cohorts of over 14 000 children whether the association between early exposure to reported mould at home in relation to respiratory and allergic diseases is modified by a single nucleotide polymorphism of the GSTP1 gene. Results We observed a positive association of mould exposure with nasal symptoms (2–10 year) aOR: 1.19 (1.02–11.38). Further, there was a borderline significant increased risk of rhinoconjunctivitis (6–8 year) in children homozygous for the minor allele Val/Val, aOR: 1.25 (0.98–1.60). In stratified analyses, subjects homozygous for the minor allele and exposed to mould at home were at increased risk for early wheezing aOR: 1.34 (1.03–1.75), whereas the major allele may confer susceptibility for later nasal outcomes, (6–8 year) aOR: 1.20 (1.00–1.45) and (2–10 year) aOR: 1.30 (1.04–1.61), respectively. For none of the health outcomes studied, we found gene by environment interactions. Conclusion A genetic influence of the GSTP1 gene cannot be ruled out, but the magnitude of the effect is a matter of further research. In conclusion, the interplay between gene and environments is complex and remains subject of further study.